Explanation:
Do the steps that I did on Problem A for each!!!!
A:-3(4-3p)
a=-3, b=4, c=3p
Apply the distributive law:
![-3*4-(-3)*3p](https://img.qammunity.org/2022/formulas/mathematics/college/tygdcth6sktlc7w9lfaec66d9eaotdt5ha.png)
Add minus - plus rules:
![-3*4+3*3p](https://img.qammunity.org/2022/formulas/mathematics/college/sbjkmoh9jh4381t3u0y04h456n6nll2a1l.png)
Simplify:
=
![-12+9p](https://img.qammunity.org/2022/formulas/mathematics/college/e2x7ckiuy79vxmnhujosqxrdtnur73xktf.png)
B:-3(7-6u)
a=-3, b=7, c=6u
=-3*7+3*6u
Simplify;
=
![-21+18u](https://img.qammunity.org/2022/formulas/mathematics/college/ul8gnzx7swr7hqyk3yvhmen7v9e8pta6sv.png)
C:-6(-1+2c)
a=-6, b=-1, c=2c
=-6(-1)+(-6)*2c
=6*1-6*2c
Simplify:
=
![6-12c](https://img.qammunity.org/2022/formulas/mathematics/college/8ql44har20d4u3fqod21iol86nrayu7219.png)
D:6(-n+7)
a=6,b=-n,c=7
=6(-n)+6*7
=-6n+6*7
Simplify:
=--6n+42
E;9(5+3c)
a=9,b=5,c=3c
=9*5+9*3c
Simplify:
=45+27c